Miniaturized extraction and determination of swelling agents in fruits and vegetables based on deep eutectic solvent-molecularly imprinted hydrophilic resin. (1st January 2023) - Wang, Mingwei; Yan, Hongyuan; Han, Yehong; Qiao, Fengxia
Highlights: New deep eutectic solvent-imprinted hydrophilic resin (DES-MIHR) was prepared. A new pipette tip solid phase extraction by DES-MIHR adsorbent was developed. New detection method for swelling agent in fruits and vegetables was developed. Hydrogen bond, π-π interactions, spatial configuration affinities vital for detection. Recoveries from various fruits and vegetables were 81.1–102.9 % (RSD ≤ 7.1 %). Abstract: The overuse of swelling agents in fruits and vegetables has rapidly increased, resulting in food safety problems. Hence, a new method for the selective extraction and detection of thidiazuron (TDZ) and forchlorfenuron (KT30) was developed using deep eutectic solvent-molecularly imprinted hydrophilic resin (DES-MIHR) as a pipette tip solid-phase extraction (PT−SPE) adsorbent with excellent molecular recognition in aqueous matrixes. DES-MIHR interacted with TDZ and KT30 via π–π interactions and hydrogen bonding. The miniaturized PT−SPE can be performed with just 5.0 mg adsorbent, 0.3 mL water, and 0.2 mL eluent, thus having the advantage of the low consumption of adsorbent and organic reagents. The performance of the DES-MIHR−PT−SPE−high-performance liquid chromatography (HPLC) method was demonstrated with the recoveries from various fruits and vegetables being 81.1–102.9 % (RSD ≤ 7.1 %). Thereby indicating the general applicability of the developed method for the accurate determination of trace swelling agents in fruits and vegetables.